Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.12716/1001.09.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Formal Safety Assessment (FSA) for Analysis of Ship Collision Using AIS Data

Abstract: Currently, Maritime safety is the best issue in the world. International Maritime organization (IMO) have recommended FSA methodology to enhance maritime safety. In this paper, the research conducted in the Malacca Strait. Malacca Strait is an area that has a high risk for shipping navigation. Many accidents occur in the area are like collision, fire, grounding and so on. Therefore a study on improving safety in this area is very important. it is to produce an output that can be used to provide input to the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…The results of the search for ways to describe the effect of a combination of hazardous factors on the quality of navigation led to the creation of methods for a formalized assessment of navigational safety (FAS) [4][5][6].…”
Section: Methodology For Formalized Safety Assessmentmentioning
confidence: 99%
“…The results of the search for ways to describe the effect of a combination of hazardous factors on the quality of navigation led to the creation of methods for a formalized assessment of navigational safety (FAS) [4][5][6].…”
Section: Methodology For Formalized Safety Assessmentmentioning
confidence: 99%
“…To verify the validity of the prediction framework, a case study was performed at the western entrance of the Malacca Strait, which is the busiest water area of Singapore. The water area in this study is selected between 103.4° E to 103.6° E in longitude and 1.1° N to 1.2° N in latitude with the data from maritime safety research [44,45], as shown in Figure 6 and Figure 7. This area is located at the end of a traffic separation scheme.…”
Section: Data Selectionmentioning
confidence: 99%
“…Xiao X et al [5] evaluated the navigation risks in the unknown environment based on the comprehensive safety evaluation method. Zaman et al [6] achieved risk evaluation in the navigation channels using the comprehensive safety evaluation method with the accident-prone Malacca Strait as a research object. P.Tmcoo et al [7] quantitatively evaluated risks of human factors with the use of Bayesian evaluation model in order to obtain objective and authentic evaluation results.…”
Section: Introductionmentioning
confidence: 99%